Agravos bucais em crianças e adolescentes com paralisia cerebral: Fatores associados e impactos na qualidade de vida - Cardoso, Andreia Medeiros Rodrigues (2017)
The assessment of factors associated with oral diseases and of their impact on the quality of life of children and adolescents with Cerebral Palsy (CP) is needed to provide an overview of this population‟s oral health condition. This study aimed to assess the prevalence of, and factors associated with, malocclusion among children and adolescents with CP. Their Health-Related Quality of Life (HRQoL) and Oral Health Related Quality of Life (OHRQoL) as well as the impact of malocclusion on their OHRQoL from caregivers' perception, were further described. This was a cross- sectional study including 149 individuals aged 2 to 18 years, institutionalized in the city of João Pessoa, Paraíba, and their caregivers. Clinical data regarding CP were obtained from medical charts, while caregivers provided socioeconomic, behavioral, systemic, HRQoL (PedsQL 4.0) and OHRQoL (PedsQL 3.0 Oral Health) information through an interview. All the participants were checked by a calibrated examiner (K = 0.72-1.00) for dental caries (dmft and DMFT), periodontal condition (GBI and CPI), occlusal condition (malocclusion and DAI), and frequency of dental traumatism (DT). The HRQoL and OHRQoL scores were transformed on a 0-100 scale and dichotomized into absence or presence of impact (Score <50). Mann-Whitney and Kruskal-Wallis, were used to compare DAI scores and HRQoL and OHRQoL questionnaires. Bivariate and multivariate analysis of Poisson Regression was applied to check for possible associations (α = 0.05). The evaluation of malocclusion in deciduous and mixed dentitions (n=108) revealed increased overjet (74.8%), anterior open bite (49.1%), posterior crossbite (21.0%), and anterior crossbite (2.8%). The presence of increased overjet was associated with lip hypotonia (PR=1,63, 95%IC=1,08-2,45) and moderade communication ability (PR=0,79; 95%IC=0,68-0,91). Open bite was associated with lip interposition (PR=1,57; 95%IC=1,10-2,26) and non-suctioning of the pacifier after the first 24 months (PR= 0,67; 95%IC=0,48-0,95). Ninety-five percent of the individuals with permanent dentition (n=40) presented severe or very severe malocclusion. DAI scores were higher among subjects with tetraparesis or diparesia, mouth breathing, liquid consistency feeding, lip hypotonia and among those who underwent pacifier suction until the age of 24 months or older (p <0.05). The mean HRQoL score was found to be 50.3 ± 10.2, with a greater impairment of physical appearance (28.2 ± 16.7), whereas the mean OHRQoL score was 78.0 ± 24.6. The frequency of CP impact on the OHRQoL was 12.1% and its presence was associated with the female gender, age range 10 to 18 years, presence of gastroesophageal reflux, and dental caries (p<0.05). It is concluded that individuals with CP had a high prevalence of malocclusion as well as systemic and behavioral associated factors. In addition, children and adolescents with CP had low HRQL scores, mainly in the physical domain. The frequency of impact on the OHRQoL was low and mostly associated with gender, age, gastroesophageal reflux and dental caries.